Occurrence and genotypes of Cryptosporidium spp., Giardia duodenalis, and Blastocystis sp. in household, shelter, breeding, and pet market dogs in Guangzhou, southern China - Liao, Shenquan (Sci Rep, 2020)
Cryptosporidium spp., Giardia duodenalis, and Blastocystis sp. are common intestinal protozoans that infect humans and animals worldwide. A survey that assessed the prevalence, molecular characteristics, and zoonotic potential of these pathogens was conducted on a variety of dogs in Guangzhou, southern China. A total of 651 canine stool samples from household (n = 199), shelter (n = 149), breeding (n = 237), and pet market dogs (n = 66) were collected from eight districts in Guangzhou. Cryptosporidium spp., Giardia duodenalis, and Blastocystis sp. were detected by PCR amplification of the SSU rRNA gene. Giardia duodenalis-positive specimens were further assigned into assemblages using the glutamate dehydrogenase gene. Cryptosporidium spp., G. duodenalis, and Blastocystis sp. were found in 21 (3.2%), 20 (3.1%), and 35 (5.4%) samples, respectively. The overall prevalence of shelter dogs (40.28%, 60/149) was significantly higher than that of household (3.0%, 6/199), breeding (2.1%, 5/237), and pet market dogs (7.5%, 5/66) (χ(2) = 154.72, df = 3, P < 0.001). Deworming in the past 12 months had a strong protective effect on the risk of contracting parasite infections (P < 0.001). No significant differences were detected between age or sex groups (P > 0.05). Dog-specific C. canis (n = 19) and zoonotic C. parvum (n = 2) were the only two Cryptosporidium species. Sequence analysis revealed the presence of three G. duodenalis assemblages: dog-specific assemblages D (n = 14) and C (n = 5), and cat-specific F (n = 1). Zoonotic Blastocystis ST3 (n = 28) was the dominant subtype, followed by ST1 (n = 6) and ST10 (n = 1). To our knowledge, this is the first large-scale investigation on the occurrence and molecular characteristics of Blastocystis sp. in dogs in China. Our results indicated that the dogs seemed to play a negligible role as reservoirs for Cryptosporidium spp. and G. duodenalis transmission to humans, but they are potential novel suitable hosts of Blastocystis sp. A strict sentinel surveillance system of dogs should be established to minimise the zoonotic risk of spreading blastocystosis among humans and dogs.